Information control by public punishment: The logic of signalling repression in China. (July 2021) - Ruan, Lotus; Knockel, Jeffrey; Crete-Nishihata, Masashi
When does repression of online expression lead to public punishment of citizens in China? Chinese social media is heavily censored through a system of intermediary liability in which the government relies on private companies to implement content controls. Outside of this system the Chinese authorities at times utilize public punishment to repress social media users. Under China's regulatory environment, individuals are subject to punishment such as fines and detention for their expressions online. While censorship has become more implicit, authorities have periodically announced cases of repression to the public. To understand when the state escalates from censoring online content to punishing social media users for their online expressions and publicizes the punishment, we collected 468 cases of state repression announced by the authorities between 1 January 2014 and 1 April 2019. We find that the Chinese authorities most frequently publicize persecutions of citizens who posted online expression deemed critical of the government or those that challenged government credibility. These cases show more evidence of the state pushing the responsibility of 'self-regulation' further to average citizens. By making an example of individuals who post prohibited content even in semi-public social media venues, the state signals strength and its determination to maintain authority.